2007
DOI: 10.1083/jcb.200702031
|View full text |Cite
|
Sign up to set email alerts
|

Cdk2 is critical for proliferation and self-renewal of neural progenitor cells in the adult subventricular zone

Abstract: We investigated the function of cyclin-dependent kinase 2 (Cdk2) in neural progenitor cells during postnatal development. Chondroitin sulfate proteoglycan (NG2)–expressing progenitor cells of the subventricular zone (SVZ) show no significant difference in density and proliferation between Cdk2−/− and wild-type mice at perinatal ages and are reduced only in adult Cdk2−/− mice. Adult Cdk2−/− SVZ cells in culture display decreased self-renewal capacity and enhanced differentiation. Compensatory mechanisms in peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
81
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 54 publications
(87 reference statements)
5
81
0
1
Order By: Relevance
“…Our studies demonstrate that, at any postnatal age, at least 50% of the NG2 + cells in the SVZ are proliferative and that Cdk2 is a major molecular regulator of their proliferation throughout postnatal development (Belachew et al, 2002;Jablonska et al, 2007). The results of our previous studies also defined the following cellular and molecular properties of NG2 + cells in the SVZ Jablonska et al, 2007): i) NG2 + cells are found scattered through the wall of the lateral ventricle, but they are more abundant in the anterior SVZ; ii) NG2 + cells in the SVZ constitute approximately 12% and 3% of the total cell population at P8 and P30-60, respectively; iii) NG2 + cells in the SVZ are highly proliferative, as demonstrated by the percentages of NG2 + Ki67 + cells in the SVZ -56 and 32% at P8 and P30, respectively; iv) NG2 + cells of the SVZ express cellular markers of neural progenitor cells and stem cells, including the Lewis X antigen (LeX) (Capela and Temple, 2003), and the transcription factors Mash1, Olig2, and Dlx (Doetsch et al, 2002;Parras et al, 2004;Marshall et al, 2005;Menn et al, 2006;Kohwi et al, 2007;Parras et al, 2007); and v) NG2 + cells of the SVZ display a type-C cell phenotype, including expression of the EGFR, PSA-NCAM, and nestin (Capela and Temple, 2002;Doetsch et al, 2002). Consistent with our findings, other reports have also described the presence of NG2 + cells in the SVZ, and demonstrated diverse cellular and molecular properties of these progenitors in this neurogenic region, including co-expression of DCX Tamura et al, 2007), responsiveness to sonic hedgehog (Loulier et al, 2006), and Islet-1-induced migration into striatum (Rogelius et al, 2006).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Our studies demonstrate that, at any postnatal age, at least 50% of the NG2 + cells in the SVZ are proliferative and that Cdk2 is a major molecular regulator of their proliferation throughout postnatal development (Belachew et al, 2002;Jablonska et al, 2007). The results of our previous studies also defined the following cellular and molecular properties of NG2 + cells in the SVZ Jablonska et al, 2007): i) NG2 + cells are found scattered through the wall of the lateral ventricle, but they are more abundant in the anterior SVZ; ii) NG2 + cells in the SVZ constitute approximately 12% and 3% of the total cell population at P8 and P30-60, respectively; iii) NG2 + cells in the SVZ are highly proliferative, as demonstrated by the percentages of NG2 + Ki67 + cells in the SVZ -56 and 32% at P8 and P30, respectively; iv) NG2 + cells of the SVZ express cellular markers of neural progenitor cells and stem cells, including the Lewis X antigen (LeX) (Capela and Temple, 2003), and the transcription factors Mash1, Olig2, and Dlx (Doetsch et al, 2002;Parras et al, 2004;Marshall et al, 2005;Menn et al, 2006;Kohwi et al, 2007;Parras et al, 2007); and v) NG2 + cells of the SVZ display a type-C cell phenotype, including expression of the EGFR, PSA-NCAM, and nestin (Capela and Temple, 2002;Doetsch et al, 2002). Consistent with our findings, other reports have also described the presence of NG2 + cells in the SVZ, and demonstrated diverse cellular and molecular properties of these progenitors in this neurogenic region, including co-expression of DCX Tamura et al, 2007), responsiveness to sonic hedgehog (Loulier et al, 2006), and Islet-1-induced migration into striatum (Rogelius et al, 2006).…”
Section: Discussionmentioning
confidence: 70%
“…We have previously demonstrated that NG2 + progenitors proliferate in the SVZ throughout postnatal development into adulthood Aguirre et al, 2005;Aguirre et al, 2007;Jablonska et al, 2007). Lysolecithin (LPC)-induced focal demyelination of the CC induced activation of SVZ cells, promoting both proliferation and migration of NG2 + progenitors into the CC .…”
Section: Retroviral Infection Of Ng2-expressing Progenitor Cells In Tmentioning
confidence: 99%
“…Previously, cdk2 was shown to be critical for the proliferation and self-renewal of neuronal progenitor cells. 46 Thus we compared the cdk2 activity using phosphorylationspecific cdk2 antibodies. As shown in Figure 6d, cdk2 activation was substantially reduced in BAD-knockdown spheres when compared with those that expressed BAD.…”
Section: Resultsmentioning
confidence: 99%
“…for the latter in SVZ cell proliferation and self-renewal [70]. Since recent work by Santamaria et al [71] described a central role for Cdk1 during embryogenesis, it would be interesting to assess if Cdk1 activity also accounts for proliferation in the DG and SVZ as basal levels of both phosphorylation of pRb and cell proliferation are maintained in Cdk6 mutant brains.…”
Section: Discussionmentioning
confidence: 98%